Increased Incidence of Rhinovirus Pneumonia in Children During the COVID‐19 Pandemic in Mexico - Ortega-Vargas, Fanny Yasmin; Herrera-González, Aldo Agustin; Díaz-Torres, Ilen Adriana; Cabrera-Takane, Isamu Daniel; Bautista-Carbajal, Patricia; García-León, Miguel Leonardo; Noyola, Daniel E.; Juárez-Tobías, María Susana; Tabla-Orozco, Verónica; Martínez-Arce, Pedro Antonio; Espinosa-Sotero, María del Carmen; Martínez-Aguilar, Gerardo; et al. (Advances in Virology, 2024)
Background: Human rhinovirus (HRV), traditionally recognized as the primary etiological agent of the common cold, has become the second most important viral agent in bronchopulmonary conditions, such as pneumonia and asthma exacerbations. During the COVID‐19 pandemic, several viruses exhibited changes in their epidemiological behavior. This study aims to evaluate the clinical and epidemiological characteristics of children with HRV pneumonia before and during the pandemic in Mexico. Methods: A comparative ambispective longitudinal epidemiological study of two cohorts (prepandemic and pandemic periods) was carried out. Two databases were compared: one from 2010 to 2013 and the other from 2021 to 2023. Children under 5 years of age diagnosed with HRV pneumonia were included. Student’s t ‐test, χ 2 tests, and logistic regression were used to assess risk factors associated with severe pneumonia. Incidence density was calculated as HRV cases per 10 new cases of pneumonia per month for each year. Results: During the pandemic, the age of presentation shifted from 5 months to 16 months. There was a higher incidence of HRV pneumonia in children during the pandemic, particularly in the second half of 2021, with a peak in July and August. In addition, there was an increase in severity (53% vs. 63%, p = 0.006) and coinfections (51.3% vs. 76% p < 0.001). A higher prevalence of all risk factors was observed in the second cohort. Conclusions: During the pandemic, a shift toward older age, a higher percentage of coinfections, and increased severity associated to HRV pneumonia were observed. These findings highlight the need for the development and implementation of targeted prevention and treatment measures for HRV.